Desenvolvimento de pacote painel visual para canal de stream na plataforma Twitch TV - Freitas, Amanda Rafaella de Macedo (Brasil, 2022)
Streaming platforms allowed the expansion of the graphic design’s use, in view of custom elements that can be added on platforms and during live broadcasts. It was proposed to develop a visual panel package for a Twitch TV platform channel with representations of Amazonian regional elements. The methodology is guided by the double diamond and the methodology proposed by Munari. We proceeded with an online quiz with the owner of the channel and external participants. Prepared a proposal for a visual panel package for the “Indio Sabido” channel. Finally, an evaluation of the visual package developed with the owner of the platform and external was carried out, in order to obtain a note for the result obtained, where we sought to define the proposed objectives were satisfactorily achieved.